2007
DOI: 10.1179/joc.2007.19.4.417
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Parenteral Antibiotic Therapy for Bone and Joint Infections: An Italian Multicenter Study

Abstract: In the early eighties, the advantages of outpatient parenteral antibiotic therapy (OPAT) (reduced costs, no hospitalization trauma in children, no immobilization syndrome in elderly, reduction in nosocomial infections by multiresistant organisms) were identified in the United States, and suitable therapeutic programs were established. Currently, more than 250,000 patients per year are treated according to an OPAT program. In order to understand the different ways of managing OPAT and its results, a National OP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 10 publications
0
31
0
1
Order By: Relevance
“…A recent multicenter study found outpatient parenteral antimicrobial therapy suitable, cost-effective, and safe in bone and joint infections [5]. However, most of the population in this study received intravenous antimicrobials in hospital infusion centers rather than the community setting.…”
Section: Vascular Access Complications 11%mentioning
confidence: 55%
“…A recent multicenter study found outpatient parenteral antimicrobial therapy suitable, cost-effective, and safe in bone and joint infections [5]. However, most of the population in this study received intravenous antimicrobials in hospital infusion centers rather than the community setting.…”
Section: Vascular Access Complications 11%mentioning
confidence: 55%
“…56 Of the remaining studies that considered acceptability in OPAT patients only, most involved multiple OPAT models (and did not differentiate between them in their findings), or did not specify the model(s) under study. In general, satisfaction with treatment was very high, 2,13,27,36,[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83] including when patients had to have frequent attendance at hospital. 5,84 Commonly perceived advantages of OPAT included the ability to resume daily activities, 2,27,71,73 feelings of improved self-esteem or greater freedom and control, 67,71,73,85,86 and not having to remain in or attend hospital.…”
Section: Patient Acceptabilitymentioning
confidence: 99%
“…For methicillinresistant S. aureus (MRSA) infections following surgery, continuous outpatient perfusion of vancomycin with steady-state plasma levels of approximately 25 mg/l for several months has been used with success [79]. Teicoplanin administered once daily for very prolonged periods also appears to be efficacious [68,80]. Quinopristin-dalfopristin is active against Enterococcus faecium [including vancomycin-resistant strains; (VRE)] and S. aureus (including MRSA), but not against E. faecalis.…”
Section: Antibiotic Therapymentioning
confidence: 99%
“…To date, only ofloxacin and ciprofloxacin have been tested in combination with rifampin [60,61,67]. However, the antimicrobial spectrum of newer fluoroquinolones, such as levofloxacin (grading A-II) and moxifloxacin (grading A-III), is more promising for the treatment of staphylococcal infections [68][69][70][71][72]. In a prospective cohort study of patients with staphylococcusinfected orthopedic implants treated with a long-term oral combination of rifampin and levofloxacin, Barberan et al [73] reported an overall clinical and bacteriological success rate of 69.5% (48/69) and 80% (16/20), respectively.…”
Section: Antibiotic Therapymentioning
confidence: 99%
See 1 more Smart Citation